The Conquest of North Africa (Libya) in the Perspective of the British Orientalist Hugh Kennedy - Alfadhili, Zainab Kazem Abd AL Hassan; Mahmmoud, Laith Shaker (Al-Adab Journal, 2023)
This study came in order to reveal the role of oriental studies in the studies of the Islamic conquest of North Africa and its stages from the point of view of the contemporary British orientalist Hugh Kennedy and to form a comprehensive picture of him through the study of Arab primary sources, as they presented accurate studies on the most important media and leaders of the conquest, and the importance of this The study sheds light on most of the events he dealt with about the conquest of the Maghreb, the most important events that took place during the conquest and the policy of the leaders in conquest, as well as their view of conquest, which they call the term (invasion) and at other times (occupation), and most of them realized the historical importance of the events despite the conflicting Arab accounts in Set dates for unlocking some cities.